Sistem Informasi Manajemen Kepegawaian di Akademi Kebidanan Ibrahimy Menggunakan PHP dan MySQL - Nurul Faizah (Department of Science and Technology Ibrahimy University, 2019)
Employee processing of official staff management at AKBID Ibrahimy covers some processing which include the processing of employee agreement, vacation and work permit request, the submission of the employee resignation, employee assessment, the issuance of employee and employer retirement warning. This activity is supporting the needs of the employment division that are still not computerized in the processing of employee management, the Head of employee devision as the person in charge of the processing of employee management in AKBID Ibrahimy can’t work effectively for processing of related documents. Based on the problems happened at AKBID Ibrahimy in processing employee management mentioned above, in order to help minimize these problems are needed the design of Management Information Systems at the AKBID Ibrahimy. This information system is expected to help simplify the processing of employee management in AKBID Ibrahimy. The system is designed using waterfall method with several steps being taken from the Requirement to Maintenance and made with PHP language programming and MySQL. From the results of this study are expected to resolve the management processing problems that has been happening. The test results as a benchmark whether the system is running well or not. Suistability employee management information system design can help the processing of employee management in AKBID Ibrahimy.